Image analysis of non aqueous phase liquid migration in aggregated kaolin - Chin, Pei Qi (2015)
Laboratory experiments have been conducted using NAPL in a three-dimensional rectangular acrylic model to study the migration of NAPL in double porosity soil. Double porosity is an important feature in soil due to its influence on the migration of liquids within the soil. NAPL is used as there is less research carried out to investigate the flow of immiscible liquid in double porosity soil. Toluene has been used as NAPL and aggregated kaolin have been utilized as double porosity soil. Experiments were carried out to observe the migration of NAPL by obtaining the area of migration liquid, the saturation of NAPL as well as the intensity of NAPL during migration. The experiments were conducted using kaolin aggregates with three different moisture contents which were 28%, 30% and 32% respectively. An image analysis procedure is used to analyze the migration of NAPL in aggregated kaolin as well as determining the effect of different moisture contents of aggregated kaolin in migration of NAPL. The experimental results from image analysis have shown that the migration of NAPL will increase as the moisture content increases. In conclusion, image analysis is capable of observing and visualizing the migration of NAPL based on saturation, intensity and area invaded by the NAPL in double porosity soil.